PENGARUH PENGGUNAAN TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS DRAMA SATU BABAK SISWA KELAS VIII SMA NEGERI 11 PADANG - Rahmadani, Meri; R., Syahrul; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT This article was written to illusstrate the effect of using technic copy the master writing skill of drama text of VIII students of SMP Negeri 11 Padang. This research data is a score in the skills of writing drama text before and after using technic copy the master. This study has three results. First, the skill of writing the text of drama of class VIII students of SMP Negeri 11 Padang before using copy the master technique is in qualification Labih of Enough (LdC) with average value 65,63. Second, the skill of writing the text of the drama of class VIII students of SMP Negeri 11 Padang after using the copy of the master is in the qualification of Good Qualification (B) with an average score of 76.91. The third is based on t-test, alternative hypothesis H1 accepted at significant level 95% and degrees of freedom (dk) = (n-1) because ttabel<thitung (1,70<3,68). Based on the result of the research, it is concluded that the skill of writing the text of drama of class VIII students of SMP Negeri 11 Padang after using copy the master technique is better than before using copy the master technique. Thus, copy the master technique can be applied as an alternative in learning skill writing text. Kata kunci: pengaruh, teknik Copy the Master, teks drama